Determinants of Antenatal Care Utilization Among Childbearing Women in Burkina Faso - Badolo, Hermann; Bado, Aristide Romaric; Hien, Hervé; De Allegri, Manuela; Susuman, Appunni Sathiya (Frontiers in Global Women's Health, 2022)
Introduction Antenatal care (ANC) is one of the pillars of maternal and child health programs aimed at preventing and reducing maternal and child morbidity and mortality. This study aims to identify the factors associated with ANC use, considering both health care demand and supply factors in the single analysis. Methods We used data from the endline survey conducted to evaluate the impact of the performance-based financing (PBF) program in Burkina Faso in 2017. This study was a blocked-by-region cluster random trial using a pre–post comparison design. The sample was derived in a three-stage cluster sampling procedure. Data collection for the endline surveys included a household survey and a facility-based survey. Women of childbearing age who gave birth at least once in the past 2 years prior to this survey and residing in the study area for more than 6 months were included in this study. Multilevel statistical techniques were used to examine individual and contextual effects related to health care demand and supply simultaneously and thus measure the relative contribution of the different levels to explaining factors associated with ANC use. Results The working women were five times [odd ratio (OR): 5.41, 95% confidence intervals (CI) 4.36–6.70] more likely to report using ANC services than the women who were not working (OR: 5.41, 95% CI 4.36–6.70). Women living in a community with high poverty concentration were 32.0% (OR: 0.68, 95% CI 0.50–0.91) less likely to use ANC services than those in a community with low poverty concentration. Women living in a community with a medium concentration of women's modern contraceptive use were almost two times (OR: 1.88, 95% CI 1.70–2.12) more likely to use ANC services than those living in a community with a low concentration of women's modern contraceptive use. Women living in the health area where the level of ANC quality was high were three times (OR: 2.96, 95% CI 1.46–6.12) more likely to use ANC services than those in the health area where the ANC quality was low. Conclusion Policies that increase the opportunity for improving the average ANC quality at the health facility (HF), the level of women's modern contraceptive use and women employment would likely be effective in increasing the frequency of use of antenatal services.